Persepsi Siswa Terhadap Radiasi Handphone dan Dampaknya Terhadap Disiplin Belajar Ditijau Dari Ilmu Sains - Vina Zulviana Nafilla; Nur Elizah; Probo Anggara; Salsabillah Shiva Putri; I. Ketut Mahardika; Singgih Baktiarso (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to find out how much students understand the concept of radiation produced by mobile phones and how the impact of radiation on health and student learning outcomes when excessive use of mobile phones. The type of research used is descriptive qualitative research. The research subjects were 10 class XII students from MAN 3 Banyuwangi, SMAN 1 Kencong, SMA Muhammadiyah 3 Jember, and SMAN 1 Tempeh Lumajang for the 2022-2023 academic year. This research was conducted online via google form. The research instrument used was a seven-item questionnaire in the form of multiple choice questions and questions with short answers. These questions must meet the discussion indicators regarding the concept of radiation, the effects of radiation on health, and the effects of radiation on learning outcomes. The results showed that students' understanding of the concept of radiation produced by mobile phones was very good with a percentage of 100%. While the impact of radiation on health that students experience varies from easily tired bodies, disturbed sleep patterns, dizziness, and eye disorders. Meanwhile, the impact of radiation on student learning outcomes when excessive use of mobile phones is loss of concentration and lazy activities so that learning outcomes will decrease. This research will give readers an idea of ​​how much students understand radiation. In addition, this study will provide an overview of what readers should do regarding the radiation generated by mobile phones on students at the high school level.